Genetic hitchhiking versus background selection: the controversy and its implications - Stephan, Wolfgang (The Royal Society, 2010)
The controversy on the relative importance of background selection (BGS; against deleterious mutations) and genetic hitchhiking (associated with positive directional selection) in explaining patterns of nucleotide variation in natural populations stimulated research activities for almost a decade. Despite efforts from many theorists and empiricists, fundamental questions are still open, in particular, for the population genetics of regions of reduced recombination. On the other hand, the development of the BGS and hitchhiking models and the long struggle to distinguish them, all of which seem to be a purely academic exercise, led to quite practical advances that are useful for the identification of genes involved in adaptation and domestication.